Vegetarian or gluten-free diets in patients with inflammatory bowel disease are associated with lower psychological well-being and a different gut microbiota, but no beneficial effects on the course of the disease. Issue 6 (July 2019) - Schreiner, Philipp; Yilmaz, Bahtiyar; Rossel, Jean-Benoît; Franc, Yannick; Misselwitz, Benjamin; Scharl, Michael; Zeitz, Jonas; Frei, Pascal; Greuter, Thomas; Vavricka, Stephan R; Pittet, Valérie; Siebenhüner, Alexander; et al.
Background: Many inflammatory bowel disease (IBD) patients follow a restrictive diet due to perceived positive effects on their symptoms. We assessed the prevalence of vegetarian (VD) and gluten-free diets (GFDs) in IBD patients, the reasons for following such a diet, and whether nutrition has an impact on disease activity and microbiota composition. Methods: We included 1254 patients from the Swiss Inflammatory Bowel Disease Cohort Study with prospective acquisition of clinical data and psychosocial, disease-related and lifestyle factors between 2006 and 2015. Dietary habits were assessed through a self-report questionnaire. In 92 patients, we analysed intestinal mucosa-associated microbial composition using high-throughput sequencing. Results: Overall, 4.1% ( n = 52) of the patients reported following a VD and 4.7% ( n = 54) a GFD. No differences regarding disease activity, fistula, hospitalization or surgery rates were observed. Patients on a VD or GFD had significantly higher levels of post-traumatic stress symptoms. Furthermore, GFD patients had significantly higher anxiety and depression symptom levels. The gut microbiota composition in IBD patients following a VD or GFD was significantly different compared to that of omnivores. Conclusions: Although we did not identify a relevant impact of a specific diet on the course of the disease, there was a significant association with lower psychological well-being in VD and GFD patients.